Selected aspects of functional efficiency and own effectiveness in patients with diabetes type 2 - Rybka, Mariola; Haor, Beata (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2018)
Introduction Diabetes is a metabolic disorder characterized by a defect in the secretion of insulin hormone. In Poland, more than 3 million people suffer from diabetes and the incidence of high blood pressure is high. The proportion of patients with geriatric age over 65 years is 25-30%. This is a group of patients characterized by multichromatism requiring a holistic approach in the treatment process. Self-efficacy is an important predictor of treatment and convalescence in patients with chronic disease. It allows them to accept the disease and learn how to function with it. Aim The aim of this study was to analyse functional level and self-efficacy in geriatric patients with type 2 diabetes. Material and methods The study was performed in patients with type 2 diabetes. 100 patients were hospitalized. The diagnostic survey method was used. The questionnaire was used for the Katz scale. On the other hand, a questionnaire on the Generalized Efficacy Scale (GSES) was used to assess the degree of value of the general belief of a person with self-efficacy in coping with difficult circumstances and adversities. The significance of the results was tested using a nonparametric chi square test. The arithmetic mean and standard deviation were also used. The correlation between the two variables was calculated by R. Spearman’s correlation coefficient. Results In the study group of 100 elderly patients with type 2 diabetes mellitus, the level of self-efficacy was statistically significantly different between the sex of the respondents and their level of education. A higher level of self-efficacy was reported among men. Conclusions Sociodynamic variables partly differentiate the level of self-efficacy of seniors with type 2 diabetes. Only the gender and education level of respondents have a significant impact on self-efficacy. Physiological variables, such as sex and age, education also affected physical fitness. With age, the degree of independence of seniors decreased. Men did better in complex activities compared to women.